DSS effectiveness: evaluation of Cimplicity Tracking System (CTS) at PMSB / Raihani Mohamed - Mohamed, Raihani (2013)
Making decisions is indeed important for organization to excel and compete with other organizations in the industry. They need to use the robust technology and latest information system to support their needs. However these systems are never being measured its effectiveness in most areas. Past literatures indicated that there are a limited number of academic studies concerned with the evaluation of domain technology-specific DSS, compared to the efforts within the business world. There are even less concerned with the evaluation of DSS in a manufacturing sector. Hence, this research is attempts to study the DSS used in supply chain environment specifically at Perodua Manufacturing Sdn. Bhd. (PMSB) called Cimplicity Tracking System (CTS) that have been used by the production executives but never being measured its effectiveness. It is also to find issues and barriers which are actual problem of the system implementation being faced. Understanding the issues is vitalto identify areas for system improvement as the company needed to improvise in order to increase the level of decision maker satisfaction and provide the decision making more effective. The result is significant for the company's system future improvement in term of quality, efficiency and satisfaction after or while using the DSS system. However, further evaluations on other system area are essential with wider population and variable approach could be performed to apprehend the evaluation on system effectiveness of the company.